ISTH guidelines for antithrombotic treatment in COVID‐19 - Schulman, Sam; Sholzberg, Michelle; Spyropoulos, Alex C.; Zarychanski, Ryan; Resnick, Helaine E.; Bradbury, Charlotte A.; Connors, Jean Marie; Falanga, Anna; Iba, Toshiaki; Kaatz, Scott; Levy, Jerrold H.; Middeldorp, Saskia; et al. (Journal of thrombosis and haemostasis, 2022)
Antithrombotic agents reduce risk of thromboembolism in severely ill patients. Patients with coronavirus disease 2019 (COVID‐19) may realize additional benefits from heparins. Optimal dosing and timing of these treatments and benefits of other antithrombotic agents remain unclear. In October 2021, ISTH assembled an international panel of content experts, patient representatives, and a methodologist to develop recommendations on anticoagulants and antiplatelet agents for patients with COVID‐19 in different clinical settings. We used the American College of Cardiology Foundation/American Heart Association methodology to assess level of evidence (LOE) and class of recommendation (COR). Only recommendations with LOE A or B were included. Panelists agreed on 12 recommendations: three for non‐hospitalized, five for non–critically ill hospitalized, three for critically ill hospitalized, and one for post‐discharge patients. Two recommendations were based on high‐quality evidence, the remainder on moderate‐quality evidence. Among non–critically ill patients hospitalized for COVID‐19, the panel gave a strong recommendation (a) for use of prophylactic dose of low molecular weight heparin or unfractionated heparin (LMWH/UFH) (COR 1); (b) for select patients in this group, use of therapeutic dose LMWH/UFH in preference to prophylactic dose (COR 1); but (c) against the addition of an antiplatelet agent (COR 3). Weak recommendations favored (a) sulodexide in non‐hospitalized patients, (b) adding an antiplatelet agent to prophylactic LMWH/UFH in select critically ill, and (c) prophylactic rivaroxaban for select patients after discharge (all COR 2b). Recommendations in this guideline are based on high‐/moderate‐quality evidence available through March 2022. Focused updates will incorporate future evidence supporting changes to these recommendations.